Optimal prostate-specific antigen (PSA) cut-off value and transrectal ultrasound guided prostate biopsy for the diagnosis of prostate cancer at ramathibodi hospital: The first study in southeast asia - K. Sirisopana (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2019. Background: The incidence of prostate cancer (PCa) in Southeast Asia is known to be lower than that of Western countries. Due to the small amount of data from Thailand, however, treatment guidelines have been adopted that were developed for different ethnic groups living in different environments. Objective: To create an optimum prostate specific antigen (PSA) cut-off level for performing prostate biopsy in the Thai population. Materials and Methods: Excluding patients with missing data, 1,486 transrectal ultrasound guided prostate biopsies were performed at Ramathibodi Hospital from January 2011 to January 2017. Patient data, such as age, PSA level and prostate biopsy findings, were collected. Sensitivities, specificities, positive predictive value and negative predictive value of the PSA cut-off were assessed by retrospective analysis. Results: Of the 1,486 transrectal ultrasound guided prostate biopsies evaluated, patients with PCa had a significantly higher mean age (69.34 vs. 67.71 years for PCa and non-PCa, p<0.001) and had a higher median PSA level (17.11 vs. 7.89 ng/mL for PCa and non-PCa, p<0.001) than non-PCa patients. Sensitivity, specificity and positive predictive value of the PSA cut-off levels of 4 and 10 ng/ml were 97.3%, 8.4% and 33.3% and 68.0%, 66.4% and 48.7%, respectively. While the sensitivity, specificity and positive predictive value of PSA cut-off levels of 5.5 and 11 ng/ml were 91.8%, 23.3% and 33.3% and 64.0%, 72.5% and 52.2%, respectively. Conclusion: The PSA cut-off should be increased to a level with an optimum trade-off between sensitivities and specificity. New PSA cut-off levels of 5.5 and 11 ng/mL would still detect 91.8% and 64% of cancers and refrain 23.3% and 72.5% of Thai men, respectively, from having unnecessary biopsies. Furthermore, this cut-off may be adopted for use in other Southeast Asian countries since they share similar environmental and genetic factors. More studies need to be performed to validate these findings.